Waktu Tunggu Pelayanan Resep pada Pasien Rawat Jalan di Klinik Pratama Rawat Inap FA-MITRA Warukulon - Lina Apriani; Herni Setyawati; Puspita Raras Anindita; Anugraheny Ayu Pramita (PHARMADEMICA : Jurnal Kefarmasian dan Gizi, 2023)
The waiting time for prescription drug services is the grace period from when a patient submits a prescription to receive a drug that meets the minimum standard set by the Ministry of Health. For non-compound prescriptions, the waiting time is less than 30 minutes, while for compound prescriptions, it is less than 60 minutes. The aim of this study was to determine the percentage of waiting time for outpatient prescription services at the FA-MITRA Inpatient Primary Clinic. The research was conducted using a descriptive method through direct observation and recording of waiting times for prescription services in a waiting time recording form in April 2022. The data collected included 307 non-compound prescriptions and 36 compound prescriptions. The average time needed to complete a non-compound prescription in the morning was 7.6 minutes, while the time needed to complete a compound prescription was 15.3 minutes. In the afternoon, the average time needed to complete a non-compound prescription was 9.3 minutes, while the time needed to complete a compound prescription was 19.3 minutes. Based on the results of the research, it was found that the average waiting time for prescription services at the FA-MITRA Inpatient Primary Clinic met the requirements of the minimum service standards in the hospital.